Falls Suffered by Elderly People From the Perspective of Health Care Personnel: A Qualitative Study. (July 2018) - López-Soto, Pablo J.; García-Arcos, A.; Fabbian, F.; Manfredini, R.; Rodríguez-Borrego, M. A.
An exploratory interpretative study was carried out to recognize the factors regarded by health care professionals as potential obstacles to the evaluation, prevention, and documentation of falls in persons above 65 years of age. Focus groups and questionnaires were carried out. Audio recordings were made, and these were subsequently transcribed and analyzed in accordance with the Bardin's thematic content analysis. Four focus groups of four persons were set up, and 16 questionnaires were returned. Four thematic categories were obtained. The analysis showed a lack of data in records of falls, perhaps for reasons of overwork, lack of motivation, awareness, or consistency in the registration systems in use. Health care professionals document two types of fall, depending on the elderly person's ability to carry out everyday tasks. There is not a rigorous and systematic approach for recording falls. Perspectives from health care professionals could help in analyzing the causes of falls and suggesting comprehensive preventive measures.